IMPLEMENTASI KURIKULUM TINGKAT SATUAN PENDIDLKAN (KTSP) SEBAGAI UPAYA MENINGKATKAN KETUNTASAN BELAJAR - Indriayu, Mintasih (Jurnal Inovasi Pendidikan, 2009)
This research aims at describing (1) Implementation of KTSP as effort to improve the student's learning mastery at Junior High School in Surakarta (2) The Readiness of teachers in KTSP implementation at Junior High School (3) Some factors supporting and impeding KTSP implementation as effort improve the learning mastery. The research was conducted in qualitative descriptive method. Research location was in Surakarta city. Data collecting technique was conducted through observation and interview. Analysis of data used interactive analysis with some steps, they are: (1) Collecting data; (2) Reducing data; (3) Presenting data and (4) Drawing of conclusion. Result of research showed that: (1) Implementation of KTSP in Junior High School in Surakarta has run pursuant to KTSP criteria where teachers given a right to develop their creativity in order to reach student's learning mastery (2) Readiness of teachers in KTSP implementation is addressed more in teaching learning process and in study service either classical or individual service (3) Some factors supporting KTSP implementation as effort to improve learning mastery are: students and teachers who interact and support each other in process of study and headmaster who has a right to determine policy. The obstacle factors are (1) Every class has a big amount of students (2) limited number of supporting facilities and basic facilities in learning process (3) teacher's ability in using learning instruments.